Immediate postoperative complications following coronary artery bypass grafting in patients with type 2 diabetes: A prospective cohort study. Issue 1 (January 2020) - Bano, Tarannum; Kuchay, Mohammad Shafi; Mishra, Sunil Kumar; Mehta, Yatin; Trehan, Naresh; Agarwal, Paras; Singh, Manish Kumar; Mithal, Ambrish
Abstract: Aims: Several studies in patients with type 2 diabetes mellitus (T2DM) from the United States and European countries have demonstrated a higher risk of morbidity and mortality than those without T2DM following coronary artery bypass grafting (CABG). The data from Indian patients are scarce. Therefore, this study was carried out to focus on immediate postoperative complications following CABG in Indian patients. Methods: Eighteen hundred consecutive patients who underwent elective CABG were included. Following exclusion criteria, a total of 1017 subjects were included for final analysis. 692 (68%) patients had T2DM and 325 (32%) patients had no T2DM. Data were obtained by collecting clinical data, routine biochemistry and chest imaging. Patients were followed up to 7 days postoperatively. Results: At baseline, hypertension, triple vessel coronary artery disease, chronic kidney disease and peripheral vascular disease were more common in patients with T2DM. Intraoperatively, use of blood products and intra-aortic balloon pump were more common in T2DM patients. Postoperatively, 13.2% patients with T2DM developed acute kidney injury versus 5.3% in non-T2DM group. Requirement of dialysis was not different between groups ( P  = 0.394). Pneumonia occurred in 2 patients in both groups ( P  = 0.370). Catheter-associated urinary tract infections were similar in two groups ( P  = 0.507). Mortality occurred only in one T2DM patient and none in non-T2DM group ( P  = 0.618). Conclusions: A significant number of patients with T2DM developed acute kidney injury following CABG. There was no difference in infective complications such as pneumonia and catheter-associated urinary tract infection, between the two groups.